Scripts of blackness race, cultural nationalism, and U.S. colonialism in Puerto Rico - Godreau, Isar P. (Global studies of the United States, 2015)
"The geopolitical influence of the United States informs the processes of racialization in Puerto Rico, including the construction of black places. In Scripts of Blackness, Isar P. Godreau explores how Puerto Rican national discourses about race...created to overcome U.S. colonial power...simultaneously privilege whiteness, typecast blackness, and silence charges of racism. Based on an ethnographic study of the barrio of San Antón in the city of Ponce, Scripts of Blackness examines how institutional and local representations of blackness developed from a power-laden process that is inherently selective and political, not neutral or natural. Godreau traces the presumed benevolence or triviality of slavery in Puerto Rico, the favoring of a Spanish colonial whiteness (under a hispanophile discourse), and the insistence on a harmonious race mixture as discourses that thrive on a presumed contrast with the United States that also characterize Puerto Rico as morally superior. In so doing, she outlines the debates and social hierarchies that inform the racialization of San Antón and its residents as black. Mining ethnographic materials and anthropological and historical research, Scripts of Blackness provides powerful insights into the critical political, economic, and historical context behind the strategic deployment of blackness, whiteness, and racial mixture"..